THE INFLUENCE OF GENDER AND DIGITAL GRAPHIC ORGANIZERS ON WRITING AND READING PERFORMANCE AT HIGHER EDUCATION - Elhawwa, Tazkiyatunnafs (IJEE (Indonesian Journal of English Education), 2024)
Graphic organizers (GOs) and gender were predicted as influential variables for the success of EFL instruction. The study attempted to elaborate the effect of gender and digital graphic organizers toward reading and writing at higher education. The 50 subjects were L2 learners at Islamic state institute consisting of male (n=24) and female (n=26). Tests were administered to gather data in different period of times. The experiment group was treated using digital GOs, the control class was taught using non- GOs. The two techniques were given to the participants both males and females in writing and reading class. A two-way Manova was employed to run with data. The analysis demonstrated The F value of Wilks’ Lambda for gender was , F(1, 49) = 6.765, p = 0.003; Wilks' Λ = 0. 769, eta= 0.231; digital graphic organizer was F (1, 49) = 5.474, p = 0.007; Wilks' Λ = 0. 804, eta= 0.196). This indicated that both gender and graphic organizer separately contributed to reading and writing. Since the eta squared was 0.23 (for gender) and 0.196 (for digital graphic organizers), it indicated that the effect size for gender was larger than  digital graphic organizers. Then, the p value of Wilks’ Lambda for the interaction effect between gender and digital graphic organizers toward reading and writing was p = 0.144).  This demonstrated no interaction effect between gender and digital GOs simultaneously on reading and writing at F (1,49) = 2.024, p = 0.144; Wilks' Λ = 0.917, eta= 0.083. However, partially, gender gave effect on reading and writing score and so did graphic organizers. Here, females had better achievement on reading and writing; and teaching using digital graphic organizer can improve both reading and writing.